PERALIHAN HAK ATAS TANAH PETANI MELALUI PROGRAM FOOD ESTATE DIKAITKAN DENGAN BATAS MAKSIMUM KEPEMILIKAN TANAH - MESTIKA DEWI SARI SAGALA (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Muhd Yamin2. Syafruddin Kalo3. Rudy Haposan Food Estate program is a government program to realize the national food security, based on the legal background, PP (Government Regulation) No. 18/2010 on Crop Cultivation. This program needs a wide agricultural land area. The research used juridical normative method which analyzed. The nature of the research was descriptive analytic The result of the research shows that the regulation on land acquisition of farmers’ land rights for implementing Food Security program, related to the maximum boundary of individual or legal entity land area based on Law No. 56 Prp 1960 on Regulation on Agricultural Land Area, is contrary to PP No. 18/2010. The implementation of the program in Bulungan Regency, East Kalimatan Province and in Merauke Regency is also contrary to PP No. 18/2010 concerning maximum boundary of land area which is allowed to be controlled by investors. Legal protection for land owners in the implementation of the program related to the Indonesian positive law is that land owners must not be treated arbitrarily, and the land transfer has to be carried out based on the agreement on the market price between farmers as the land owners and investors.Keywords: Food Estate, Land Transfer, Maximum Boundary of Land Area